Papan Pintar Acak Kata for Improves Reading Skills of Grade II Elementary School Students - Ni Kadek Sintayani; I Made Citra Wibawa; Putu Aditya Antara (Jurnal Ilmiah Sekolah Dasar, 2023)
The ability to read is an ability that must be possessed by students as the main capital in improving their quality. This study aims to produce learning media "Smart Board Random Words" to improve the reading skills of Indonesian language content for second grade elementary school students whose effectiveness has been tested. This study uses the ADDIE model which consists of 5 stages: analysis, design, development, implementation, and evaluation. The subject of development in this research is a product in the form of word scrambled smart board media, the object of development is content validity, user response, and product effectiveness. The test subjects in this study involved 55 grade II elementary school students, whose reading skills were used as the test object. Data collection methods and instruments used in this study were observation guidelines, interview guidelines, rating scales and questionnaires. Test product validity using the Gregory formula. Data analysis is using qualitative statistics and statistical inferential t-test technique. The results from content validation, teacher's and students' response showed that the random word smart board media obtained a very valid. The test results for the effectiveness of learning media show a result of 0.000 less than 0.05, which means that the product being developed has significant effectiveness. It was concluded that the learning media "Smart Board Random Words" can improve the reading skills of Indonesian language content for class II elementary school students.